(untitled) (Web of Teachers: Inderscience Research, 2026)
Sibling relationships are among the longest-lasting interpersonal bonds in human life, yet their cultural regulation remains insufficiently discussed in Central Asian family psychology. This article examines sibling relationships in Uzbek families through three interconnected psychological dimensions: support, rivalry, and responsibility. The paper is designed as a theoretical and conceptual study based on international sibling research and Uzbek/Russian-language scholarship on family values, intergenerational norms, and child upbringing. The main argument is that sibling relationships in Uzbek families cannot be adequately interpreted only through the categories of warmth and conflict. They are embedded in a value-oriented family system where respect for elders, care for younger family members, collective reputation, mutual assistance, and gendered expectations structure everyday interaction. Cultural values may strengthen sibling solidarity and emotional closeness, but they may also intensify rivalry when parental attention, educational opportunities, inheritance expectations, or household responsibilities are perceived as unfair. The article proposes a culturally sensitive model in which family values influence sibling support and rivalry through the mediating role of perceived responsibility and fairness. The paper contributes to family psychology by integrating classical Western theories of sibling relationship quality with Uzbek and Russian academic perspectives on family life. Practical implications are offered for family counseling, student psychological support, and preventive work with hidden conflict in extended families.